Improved Infection Control Reporting through Interactive Data Visualisation - HORPPU, MATILDA (My University, 2019)
1928 Diagnostics is a company in Gothenburg that strives to preserve the power of antibiotics by providing hospitals with a tool they can use in their work with infection control. The platform they have developed analyses NGS data and presents the results to the user in different ways. Today, the main users of the platform are microbiologists that use it for identifying disease outbreaks, among other things. An important task that the microbiologists are faced with is to report this result to the infection control unit at the hospital so that they can take action if an outbreak has occurred. Currently, the reporting step in the infection control workflow is problematic since there is a large knowledge gap between the microbiologists and the infection control unit which puts high requirements on how the tests results are communicated. Furthermore, the microbiologists have no tool that includes all information they need to include in the reports they are creating which lead to a lot of extra work. Therefore, this master’s thesis will focus on how interactive information visualisation can be used to design a tool that makes the reporting easier for the microbiologists and improves the communication with the infection control unit. Before the concept development phase a literature study of the area and user study were carried out in order to build a good foundation for the project. An iterative design process was applied to the execution phase, where each iteration consisted of idea generation, prototyping suited to the goal of the iteration, user testing and an analysis of the results. The project resulted in a set of design guidelines that should be considered a starting point for further research. The Guidelines were developed alongside a prototype that can be seen as an example of how the guidelines could be applied in a design.
Keywords: interaction design; information visualisation; infection control; NGS